Սեյդո Պողոս - Հակոբ Պետրոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлены важные моменты жизни и деятельности одного из выдающихся представителей национально-освободительной борьбы Тарона и Сасуна конца XIX начала XX-го века Сейдо Погоса. Он воевал рядом с Андраником, Геворгом Чавушом, Акопом Котояном, Корюном из Гомса, активно участвовал в боях монастыря Аракелоц (Апостолов) города Муша, деревни Сулух, Ахтамара, руководил обороной армян во время армянотатарских столкновений в 1905-1906 гг. The article presents some important fragments of the life and activity of one of the prominent representatives of Taron and Sassoun national-liberation movement Seydo Poghos in the end of XIX and the beginning of XX century. He faught together with Andranik, Gevorg Chavoush, Hakop Kotoyan, Koryoun of Goms, had an active participation in the combats of Arakelots (Apostols’) monastery of Moush, village of Souloukh, Aghtamar and headed the defense of the Armenian during the Armenian- Tatar conflicts in 1905-1906.
Keywords: History